Evaluasi Pelaksanaan Tugas Pembantuan Operasi Dan Pemeliharaan (TP-OP) Jaringan Irigasi Pada Satker Dinas Pengairan Dan Pemukiman Provinsi Lampung Tahun Anggaran 2009 Dan 2010 - Zaldi Ronald; Dyah Indriana Kusumaastuti; Sumiharni . (UNIVERSITAS LAMPUNG, 2012)
The evaluation of the execution of TP-OP of the irrigation system on working unit of irrigationand settlement agency of Lampung province in 2009 and 2010 is reviewed from the aspect of itsestimation and execution to give an illustration of the performance of the working unit with sourceof funds in APBN. In 2009 the budget estimation is Rp. 20.566.050.000 and in 2010 with thebudget estimation is Rp. 21.937.120.000, whicht each year has different problem and situation.This is proven by the absorb total budget estimation which is only 83,98% in 2009 and 97,75% in2010. The distinction of the problem and situation faced by working unit in every fiscal year willgive positive and negative impact which will be analyzed for the sake of a sustainableimprovement for TP-OP program.